2018
DOI: 10.3389/fmed.2018.00141
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Benefit of “Balanced Diet” for Rheumatoid Arthritis

Abstract: Although it is largely unknown how diet might modulate rheumatoid arthritis (RA), dietary interventions, including so-called “low-carbohydrate” diets, may be considered for RA patients because of the high incidence of cardiovascular comorbidity. However, it has been shown that restriction or skewed intake of particular nutrient may alter the components of the intestinal flora. Changes to the gut microbiota or dysbiosis may be relevant to the pathogenesis of RA because the gut microbiota is reported to regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 36 publications
0
38
0
4
Order By: Relevance
“…In spite of the growing evidence of the relationship between diet and RA symptoms, research in the field is still limited to mostly observational studies; however, there are quite a few interventional studies in which diet has been evaluated as a strategy to improve RA symptoms. A detailed review of the studies can be found here [206][207][208]. Most interventions combine a diet with high intake of vegetables, fruit, and antioxidants with periods of fasting.…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 99%
“…In spite of the growing evidence of the relationship between diet and RA symptoms, research in the field is still limited to mostly observational studies; however, there are quite a few interventional studies in which diet has been evaluated as a strategy to improve RA symptoms. A detailed review of the studies can be found here [206][207][208]. Most interventions combine a diet with high intake of vegetables, fruit, and antioxidants with periods of fasting.…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 99%
“…BMI ≥30 kg/m 2 ) is a risk factor for developing RA [7]; obese RA patients have higher disease activity, greater joint pain and more associated diseases [43]. As for effects of underweight, rheumatoid sarcopenia, rheumatoid cachexia, and metabolic syndrome, nowadays they are subjects of a number observational studies [16].…”
Section: лекції огляди / Lectures Reviewsmentioning
confidence: 99%
“…Speaking on pathogenesis of most rheumatic diseases (such as connective tissue diseases (CTDs), spondyloarthritis (SpА), and systemic vasculitis), the environmental factors (chemical, physical, infectious ones, as well as nutrition, tobacco smoking, psycho-emotional stress, alcohol consumption, drug use and microbiota changes) are mainly seen as triggers for realizing the effects of genetic risk factors for the development of autoimmune disorders [8][9][10][11][12][13]. Nevertheless, more attention is paid to study of the environmental factors' effects [14][15][16][17][18][19]. Up to 30-60 % of the risk of developing rheumatoid arthritis (RА) is considered to be related to genetic predisposition, while 40-70 % of this risk seems to be associated with the environmental factors' effects, and the magnitudes of their effects depend on age and gender of the patients [20][21].…”
mentioning
confidence: 99%
“…Rezidive traten im Verlauf der Studie nicht auf. Auch wenn die Anzahl der Probandinnen relativ klein war konnte mit der Studie gezeigt werden, dass eine Exazerbation der Grunderkrankung durch Sport nicht zu erwarten ist und zudem eine positive Beeinflussung der Entzündung anzunehmen ist (35).…”
Section: Sport Und Autoimmunitätunclassified
“…Verschiedene Daten legen na-he, dass eine Ernährung mit einem verminderten Gehalt an Eiweißen, Kohlehydraten und/oder Zucker, bzw. eine vegetarische oder gar vegane Diät einen günstigen Einfluss auf rheumatische Erkrankungen haben könnte (34)(35)(36). Des Weiteren scheinen ungesättigte Fettsäuren wie in Olivenöl (Mediterrane Diät) möglicherweise einen positiven Effekt zu haben (37).…”
Section: Interaktion Mit Anderen Lebensstilfaktorenunclassified